(untitled) (Revista Brasileira Multidisciplinar, 2010)
This article discusses how the notion of sustainable development in today’s globalized world is being appropriated, legitimized and exploited, as well as the criticism that this construct is suffering. We have used categories of analysis which were constructed from critical theoretical references. The work hypothesis shows that sustainable development does not focus on the main elements of environmental degradation and that the options of the peripheral countries are not reversing the picture of nature destruction. To address this issue a review of published scientific literature on the environmental issue in general and sustainability in particular has been done. The conclusion points to the clue that real sustainable actions depend critically on the level and quality of public consciousness, on their perception of reality and experienced problems, and on their organizational skills to promote changes in this direction.